1988
DOI: 10.1523/jneurosci.08-12-04734.1988
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of protein kinase C isozymes in rat brain

Abstract: Recently, we isolated 3 protein kinase C (PKC) isozymes from rat brain (Huang et al., 1986a). Using isozyme-specific antibodies for immunoblot, we have determined the relative levels of each isozyme in various regions of the rat brain (Huang et al., 1987b). The present paper describes the cellular distributions of PKC isozymes in rat brain as determined by light microscopic immunocytochemistry. Staining with PKC antibodies revealed strong immunoreactivities in neuronal somata and their dendrites and weak to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
128
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(137 citation statements)
references
References 30 publications
9
128
0
Order By: Relevance
“…In this respect, PLC␤4 mutant mice share a common phenotype with previously reported mutant mice with inactivated mGluR1, G␣q, or PKC␥ gene (14,15,16). mGluR1, G␣q, and PKC␥ all are expressed abundantly and homogeneously in adult wild-type PCs; mGluR1 is localized on the perisynaptic membrane of PC dendritic spines (4,5), G␣q͞11 is on the extra-junctional membrane of PC dendritic spines (S. Nakagawa, J. Tanaka, M.W., M.K., M.I.S., and Y.I., unpublished data), and PKC␥ is in the cytoplasm of PC dendrites and somata (8,9,10). In the present study, we found that expression of PLC␤4 mRNA is heterogeneous in the rostrocaudal and mediolateral axes (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, PLC␤4 mutant mice share a common phenotype with previously reported mutant mice with inactivated mGluR1, G␣q, or PKC␥ gene (14,15,16). mGluR1, G␣q, and PKC␥ all are expressed abundantly and homogeneously in adult wild-type PCs; mGluR1 is localized on the perisynaptic membrane of PC dendritic spines (4,5), G␣q͞11 is on the extra-junctional membrane of PC dendritic spines (S. Nakagawa, J. Tanaka, M.W., M.K., M.I.S., and Y.I., unpublished data), and PKC␥ is in the cytoplasm of PC dendrites and somata (8,9,10). In the present study, we found that expression of PLC␤4 mRNA is heterogeneous in the rostrocaudal and mediolateral axes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PCs express high levels of type 1 metabotropic glutamate receptor (mGluR1) (4,5), which stimulates PLC through the activation of heterotrimeric G-proteins of the G␣q͞11 family (6,7). PCs are also very rich in the ␥ isoform of protein kinase C (PKC␥) (8,9,10) and in inositol 1,4,5-trisphosphate receptors (11), both of which are activated after hydrolysis of phosphatidylinositol 4,5-bisphosphate by the PLC␤ enzymes. G␣q has been shown to colocalize with mGluR1 in PC dendritic spines (S. Nakagawa, J. Tanaka, M.W., M.K., M.I.S., and Y.I., unpublished data).…”
mentioning
confidence: 99%
“…PKC is the only known Ng kinase in vitro (5), and deletion of PKC ␥ gene in mice negates both the glutamate-and depolarization-mediated phosphorylation of Ng (9). The close functional relationship between Ng and PKC ␥ is further illustrated by their similar developmental expression patterns in the cerebral cortex (10)(11)(12). Previous studies also suggest that Ng plays a critical role in synaptic plasticity.…”
mentioning
confidence: 88%
“…13,29 We did observe a moderate signal for PKCg, an isozyme more often associated with neural tissue, which likely reflects the strong innervation of the cavernosal tissues. 30 Traditionally, PKCs were believed to reside in the cytosol in an inactive conformation and translocate to the membrane (or other subcellular sites) upon activation where they modify various cellular functions through phosphorylation of target substrates. 16,22 We observed that PKCa, b, d, andi were predominantly present in the particulate fraction of rat cavernosal smooth muscle in resting state.…”
Section: Pkc Involvement In Cavernosal Contraction S Husain Et Almentioning
confidence: 99%